Given that , find
Notation: denotes the derivative of at
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We know that g ( x ) = d x 0 . 5 d 0 . 5 ( f ( x ) )
If we take the 1 . 5 th derivative of g ( x ) , we get d x 1 . 5 d 1 . 5 ( d x 0 . 5 d 0 . 5 ( f ( x ) ) ) = d x 1 . 5 + 0 . 5 d 1 . 5 + 0 . 5 ( f ( x ) ) = d x 2 d 2 ( x 5 3 ) = − 2 5 x 5 7 6
Now we can plug in 3 2 and the answer is − 2 5 ( 3 2 ) 5 7 6 = − 0 . 0 0 1 8 7 5